Rapid Purification and Partial Characterization of an Extracellular Enantioselective Lipase from Aspergillus niger - Dominggus Malle; Gina Garingan; Milagros Peralta; Maria Jamela Revilleza (Research Center for Biotechnology - Indonesian Institute of Sciences (LIPI), 2008)
Lipases [EC. 3.1.1 .3] are capable of hydrolyzing ester bonds of triglycerides and have received much attention from protein researchers after these enzymes have shown potential applications such us, in the manufacture of commercially important chiral drugs due to their enantioselectivity properties. A novel extracellular lipase produced by Aspergillus niger was purified and partially characterized. Using the culture medium as crude extract, the Lipase was purified to 25 .7 folds after Ultrafiltration and DEAE ion exchange chromatography. The enzyme was characterized to have optimum activity at neutral pH and at 30-35°C, while its kinetic parameters, Vmax and Km, were determined to be L80 U/mL/min and 0.2 mL , respectively. SDS-PAGE analysis revealed the presence of at least two bands (±87 and ±72 kDa), while native PAGE showed a single band. The two bands could represent subunits in a complex or isoforms of the enzyme. The use of the enzyme in th hydrolysis of a racemic mixture of 2-arylpropionic butyl ester analyzed after HPLC demonstrated an apparent predominant enantioselectivity for the S (+) enantiomer. Thus, this lipase is a promising enzyme for the chiral drug preparation of single enantiomer of 2-arylpropionic acid (ibuprofen) .Keywords: Iipase, Aspergillus niger, purification, enantioselectivity, chiral drug, ibuprofen